ROM 13:1-7, SUBMISSION TO THE POLITICAL AUTHORITIES: A Literary-Rhetorical Study - Ottapurackal, Sibichen Joseph (Asian Horizons, 2013)
The pericope, ‘submission to the political authorities,’ found within the exhortative section of Romans (12:1–15:13) has contributed number of studies to support and deny its authenticity within the letter. Those, who argue against the pericope, present various literary and thematical problems within the text. They say that it is impossible for Paul to ask for submission to the authorities, because the authorities are not always acting for good and justice, but often are considered as oppressive. It is also argued that the pericope within two agape pericopes (12:9-21 and 13:8-10) interrupts the flow of the love theme. Similarly, some of its terminologies rarely occur in the Pauline writings.Thus, they accuse it as a “content buy-in” from Graeco-Roman political ideology, “an interpolation,” “material incorporated into in a later stage,” “a fully articulated doctrine of the church” and “a situational counsel.”